2021
DOI: 10.3389/fonc.2021.664714
|View full text |Cite
|
Sign up to set email alerts
|

Para-Aortic Nodal Radiation in the Definitive Management of Node-Positive Cervical Cancer

Abstract: ObjectivesTo investigate the safety and outcomes of elective para-aortic (PA) nodal irradiation utilizing modern treatment techniques for patients with node positive cervical cancer.MethodsPatients with pelvic lymph node positive cervical cancer who received radiation were included. All patients received radiation therapy (RT) to either a traditional pelvic field or an extended field to electively cover the PA nodes. Factors associated with survival were identified using a Cox proportional hazards model, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“… 85 In cervical cancer, the incidence of common iliac LNM is lower, but once common iliac LNM occurs, the OS is significantly reduced. 46 , 47 , 80 , 83 , 86 , 87 In a prospective cohort study of 560 patients at a single center, the risk of recurrent disease was shown to increase incrementally on the basis of the most distant level of LN involvement at PET, with a hazard ratio of 2.40 (95% confidence interval: 1.63, 3.52) for pelvic involvement, 5.88 (95% confidence interval: 3.80, 9.09) for para-aortic involvement, and 30.27 (95% confidence interval: 16.56, 55.34) for supraclavicular involvement. 12 …”
Section: Resultsmentioning
confidence: 99%
“… 85 In cervical cancer, the incidence of common iliac LNM is lower, but once common iliac LNM occurs, the OS is significantly reduced. 46 , 47 , 80 , 83 , 86 , 87 In a prospective cohort study of 560 patients at a single center, the risk of recurrent disease was shown to increase incrementally on the basis of the most distant level of LN involvement at PET, with a hazard ratio of 2.40 (95% confidence interval: 1.63, 3.52) for pelvic involvement, 5.88 (95% confidence interval: 3.80, 9.09) for para-aortic involvement, and 30.27 (95% confidence interval: 16.56, 55.34) for supraclavicular involvement. 12 …”
Section: Resultsmentioning
confidence: 99%
“…Treatment of these nodal regions is challenging given significant amounts of bowel, kidney, spine, and other exposed organs. Modern treatment planning including intensity-modulated radiation has allowed for more comfortable treatment of these regions generally up to the level of renal vessels, and even dose escalation around the duodenum for gross nodal disease 40. Our clinic has demonstrated the feasibility of using proton therapy for extended-field therapy in post-operative cancers15 (Figure 3).…”
Section: Para-aortic Nodal Radiationmentioning
confidence: 97%
“…Modern treatment planning including intensity-modulated radiation has allowed for more comfortable treatment of these regions generally up to the level of renal vessels, and even dose escalation around the duodenum for gross nodal disease. 40 Our clinic has demonstrated the feasibility of using proton therapy for extended-field therapy in post-operative cancers 15 (Figure 3). Treatment of the para-aortic nodes with radiation is often employed in patients with early-stage testicular seminoma, and is feasible with proton therapy.…”
Section: Para-aortic Nodal Radiationmentioning
confidence: 99%
“… 8 , 9 On the contrast, some studies indicated that prophylactic EFI did not reduce the risk of para‐aortic nodal recurrence and confer survival benefits in patients with positive pelvic lymph node cervical cancer. 10 , 11 Anyway, prophylactic EFI is considered to be safe in modern radiotherapy techniques without a significant increase in severe toxicities in patients with cervical cancer. 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 Anyway, prophylactic EFI is considered to be safe in modern radiotherapy techniques without a significant increase in severe toxicities in patients with cervical cancer. 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%